Význam TDM, fenotypizace a genotypizace pro správné dávkování léciv - Grundmann, Milan; Kacírová, Ivana (Casopis lekaru ceskych, 2010)
Therapeutic drug monitoring is a specific method of clinical pharmacology for monitoring of the therapy using measurement of drug serum concentrations followed by interpretation and good cooperation with clinician. It significantly helps to personalize and rationalize the treatment, to set individualized dosing, to minimize side effects, to decrease mortality and morbidity and to decrease the costs. Phenotyping and genotyping can increase therapeutic drug monitoring on higher level.
Keywords: Drug Monitoring; genotyp; farmakokinetika; výpočet dávky léku; Drug Dosage Calculations; Humans; Pharmacokinetics; Genotype; lidé; individualizovaná medicína; Phenotype; fenotyp; Precision Medicine; monitorování léčiv